2011
DOI: 10.2753/ijp0891-1916400202
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and the Evolution of the U.S. Financial System, 1945-1986

Abstract: The New Deal regulatory policies and institutions redesigned the u.s. financial structure and implicitly required the coordination between monetary policy and the regulatory framework; in that financial structure the Federal reserve provided the reserves. The interest policy implicitly required the calibration and coordination of deposit ceiling rates and the prevailing market rate set by the Fed. However, the Treasury-Federal reserve Accord of 1951 effectively dismantled the necessary coordination between mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Interest rate liberalization means that the pricing interest rate that financial institutions depend on is determined by market supply and demand. In his study on the U.S. banking industry from 1970 to 1986, de Rezende [2] found that financial innovation and reform of the interest rate liberalization in the U.S. were triggered by the choice of capital investment outside the bank channel, as the low deposit interest rate of banks is not appealing under the restraint of Q treaty. Xiao [3] believed that the pricing mechanism of shadow banks can better reflect the supply and demand of market funds, contributing to the marketization of RMB interest rates.…”
Section: Connotation Of Interest Rate Liberalizationmentioning
confidence: 99%
“…Interest rate liberalization means that the pricing interest rate that financial institutions depend on is determined by market supply and demand. In his study on the U.S. banking industry from 1970 to 1986, de Rezende [2] found that financial innovation and reform of the interest rate liberalization in the U.S. were triggered by the choice of capital investment outside the bank channel, as the low deposit interest rate of banks is not appealing under the restraint of Q treaty. Xiao [3] believed that the pricing mechanism of shadow banks can better reflect the supply and demand of market funds, contributing to the marketization of RMB interest rates.…”
Section: Connotation Of Interest Rate Liberalizationmentioning
confidence: 99%
“…Banks suffered from the competition by non-banks because the latter were allowed to offer higher interest rates on deposits-like assets. Banks were obliged by regulation q to offer fixed low interest rates on deposits ( see Rezende 2011, Kregel 2010. Thus in order to help them compete they were allowed to develop new products, mainly securities, on which regulation q did not apply, and then slowly the Glass-Steagall Act was abolished.…”
Section: Financial Fragility and Financial Structure In Minskymentioning
confidence: 99%